2005
DOI: 10.1017/s0954102005002841
|View full text |Cite
|
Sign up to set email alerts
|

Costa Recta beach, Deception Island, West Antarctica: a retreated scarp of a submarine fault?

Abstract: Deception Island (South Shetlands, Antarctica) is one of the most active volcanoes in Antarctica, having erupted recently in 1967Antarctica, having erupted recently in , 1969Antarctica, having erupted recently in and 1970, damaging scientific stations on the island. It is also seismically very active. The island has attracted the attention of many researchers as it constitutes an undisturbed natural laboratory to study seismo-volcanic events and how they affect landscape modelling and evolution. One of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Holohan et al (2005) described fracture sets associated with caldera collapse, pointing out that ring and radial faults control the brittle deformation, and probably determine the location of later eruptions associated with the caldera rim. The outer shoreline of the island exhibits a complex evolution, with high lava cliffs on the northern and western shorelines, and a linear coastline due to the action of submarine faulting to the east of the island (Fernández-Ibáñez et al, 2005).…”
Section: Regional Settingmentioning
confidence: 99%
“…Holohan et al (2005) described fracture sets associated with caldera collapse, pointing out that ring and radial faults control the brittle deformation, and probably determine the location of later eruptions associated with the caldera rim. The outer shoreline of the island exhibits a complex evolution, with high lava cliffs on the northern and western shorelines, and a linear coastline due to the action of submarine faulting to the east of the island (Fernández-Ibáñez et al, 2005).…”
Section: Regional Settingmentioning
confidence: 99%
“…1) is considered as a laboratory for Volcano Geophysics due to the large number of multidisciplinary studies focused both on imaging its surface and deep structures and on monitoring its volcanic activity. Scientists have widely studied the origin and morphology of Deception Island, bringing forward general and local models (e.g., Martí et al 1996Martí et al , 2013Smellie et al 2002;Fernández-Ibáñez et al 2005;Maestro et al 2007; Barclay et al 2009;Melo et al 2012;Torrecillas et al 2012Torrecillas et al , 2013. The study of the seismic activity of the volcano is probably the most active and productive research line, as reported by Tejedo et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kirkwood, the phreatomagmatic eruptions produced by these fissures and the alignments of submarine cones inside the caldera. The third system is NNW–SSE oriented and its main evidence is in the Costa Recta alignment [ Fernández‐Ibáñez et al , 2005]. Other alignments can be observed in the Mt.…”
Section: Tectonic Settingmentioning
confidence: 99%